Screening Capsicum accessions for tomato necrotic ringspot virus resistance - Puangmalai P. (2014)
A total of 52 Capsicum spp. accessions of three different species, C. annuum, C. baccatum and C. chinense, were screened against tomato necrotic ringspot virus, a new Tospovirus isolate in Thailand that causes severe yield losses in vegetable crops. A mechanical inoculation method was used to screen the accessions for resistance to the virus, and resistant plants were transplanted into a greenhouse for continued observation. The experiment was conducted in 2011 in Chiang Mai Province, Thailand. A total of eight accessions were identified with resistance to the virus: three lines of C. annuum (PY-4300, PY- 4301 and PY-4302) and five lines of C. baccatum (CA1316, CA1998, CA2000, CA2008 and CA2009).